Interpreting coral reef monitoring data: A guide for improved management decisions. (January 2017) - Flower, Jason; Ortiz, Juan Carlos; Chollett, Iliana; Abdullah, Sabah; Castro-Sanguino, Carolina; Hock, Karlo; Lam, Vivian; Mumby, Peter J.
Graphical abstract: Highlights: A framework for interpreting temporal trends in coral reef monitoring attributes is presented. A decision tree for diagnosing the stressors affecting a reef is developed using select indicators. The diagnosis is integrated with further indicators to provide a prognosis for a reef. The diagnosis and prognosis framework can be used to guide reef management actions and provide a minimal set of reef monitoring indicators. Abstract: Coral reef monitoring programmes exist in all regions of the world, recording reef attributes such as coral cover, fish biomass and macroalgal cover. Given the cost of such monitoring programs, and the degraded state of many of the world's reefs, understanding how reef monitoring data can be used to shape management decisions for coral reefs is a high priority. However, there is no general guide to understanding the ecological implications of the data in a format that can trigger a management response. We attempt to provide such a guide for interpreting the temporal trends in 41 coral reef monitoring attributes, recorded by seven of the largest reef monitoring programmes. We show that only a small subset of these attributes is required to identify the stressors that have impacted a reef (i.e. provide a diagnosis), as well as to estimate the likely recovery potential (prognosis). Two of the most useful indicators, turf algal canopy height and coral colony growth rate are not commonly measured, and we strongly recommend their inclusion in reef monitoring. The diagnosis and prognosis system that we have developed may help guide management actions and provides a foundation for further development as biological and ecological insights continue to grow.